Educators' perceptions, attitudes and practices: blended learning in business and management education - Deborah Anderson; Vladlena Benson; Ann Ooms (Association for Learning Technology, 2011)
Adoption of blended learning is a complex process for higher education institutions and academic staff. Although the move towards blended learning is generally instigated at institutional level, factors determining its success and minimising resistance of faculty often emerge at delivery level. This paper explores adoption of blended learning practices in a Business School at a university in the United Kingdom. Based on the interviews with a purposive sample of 16 academic staff members delivering 36 business modules, this case study explores the concept of blended learning from the academic staff's perspective. A typology of three distinct approaches to blended learning – ‘Technology is all', ‘Bolt-ons' and ‘Purely pedagogic' – emerged from the data extending understanding of blended learning practices. A team of three researchers conducted the study. Two of the researchers were academic staff members from the Business School and one researcher was an academic staff member from another faculty within the same university.